Migration and Skills : The Experience of Migrant Workers from Albania, Egypt, Moldova, and Tunisia - Sabadie, Jesus Alquezar; Avato, Johanna; Bardak, Ummuhan; Panzica, Francesco; Popova, Natalia (World Bank, 2012)
The subject of migration, and how best to manage it, has been moving up the policy agenda of the European Union for some time now. Faced with an aging population, possible skills shortages at all skills levels, and the need to compete for highly skilled migrants with countries such as Australia, Canada, and the United States, the European Union (EU) is moving from seeing migration as a problem or a threat to viewing it as an opportunity. As an EU agency promoting skills and human capital development in transition and developing countries, the European Training Foundation (ETF) wished to explore the impact of migration on skills development, with a special emphasis on Diasporas and returning migrants. For the World Bank, the issue of migration forms an integral part of its approach to social protection, since it believes that labor-market policy must take into account the national as well the international dimensions of skilled labor mobility. Both institutions were keen to look at what changes need to be made to migration policy in order to achieve a triple-win situation, one that can benefit both sending and receiving countries as well as the migrants themselves. This report aims to unravel the complex relationship between migration and skills development. It paints a precise picture of potential and returning migrants from four very different countries, Albania, the Arab Republic of Egypt, Moldova, and Tunisia, that is a conscious choice of two 'traditional' (Egypt, Tunisia) and two 'new' (Albania, Moldova) sending countries, and describes the skills they possess and the impact that the experience of migration has on their skills development. It is harder to draw accurate conclusions on the link between job aspirations and current employment status, since many of the potential migrants were not actively employed at the time of the interview. However, the data suggest people did expect to change jobs as a result of migration, and the sectors they expected to work in varied according to their nationality. Focusing solely on those planning to move to the EU, many Albanians expected to work in domestic service, hospitality, and construction; Egyptians expected to work in hospitality and construction; Moldovans expected to work in domestic service and construction; and Tunisians expected to work in hospitality and manufacturing. Few migrants working in agriculture or petty trade aimed to work in these same sectors while abroad.